2021
DOI: 10.3390/tropicalmed6040179
|View full text |Cite
|
Sign up to set email alerts
|

Carriage Prevalence of Extended-Spectrum β-Lactamase Producing Enterobacterales in Outpatients Attending Community Health Centers in Blantyre, Malawi

Abstract: Antimicrobial resistance due to extended-spectrum β-lactamase (ESBL) production by Enterobacterales is a global health problem contributing to increased morbidity and mortality, particularly in resource-constrained countries. We aimed to determine the prevalence of extended-spectrum β-lactamase-producing Enterobacterales (ESBL-E) in community patients in Blantyre, Malawi. Clinical samples were collected from 300 patients and screened for ESBL-E using a CHROMagarTM ESBL medium. Confirmation of ESBL production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
5
1
2
Order By: Relevance
“…There is limited information on risk factors related to the fecal carriage of EPE (31). Different surveys have indicated adverse data on the association between sex and carriage of EPE; meanwhile, our results, in line with some studies, demonstrate an association between the males with EPE carriage (9,32,33). Therefore, these discrepancies may reflect the regional habit, social activity, and employment status related to gender.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…There is limited information on risk factors related to the fecal carriage of EPE (31). Different surveys have indicated adverse data on the association between sex and carriage of EPE; meanwhile, our results, in line with some studies, demonstrate an association between the males with EPE carriage (9,32,33). Therefore, these discrepancies may reflect the regional habit, social activity, and employment status related to gender.…”
Section: Discussionsupporting
confidence: 76%
“…For the isolation of ESBL-producing E. coli (EPE), we inoculated the stool samples on CHROMagar ESBL (CHRO-Magar, Paris, France) and identified red colonies by standard microbiologic techniques (9). Susceptibility to cefotaxime (CTX; 30 µg), ceftazidime (CAZ; 30 µg), nalidixic acid (NA; 30 µg), and ciprofloxacin (CIP; 5 µg; Mast Group Ltd, Merseyside, United Kingdom) was tested using the disc diffusion method (10).…”
Section: Antibiotic Susceptibility Testingmentioning
confidence: 99%
“…Threefold increase in the prevalence of ESBL-producing Enterobacterales has been reported worldwide. [ 23 24 25 ] Identification of the underlying conditions and judicious use of appropriate antimicrobials is essential to prevent serious life-threatening conditions, such as urosepsis and renal failure. The increasing resistance to fluoroquinolones observed in E. coli (43%) and K. pneumoniae (30%) precludes their empirical use as IDSA guidelines discourage empirical use of fluoroquinolones if the local resistance is more than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite variations in study methodologies, a high rate of MRSA presence was reported, particularly in long-sleeved white coats and ties, as well as evidence of inappopriate laundering techniques. Onduru et al, found a rate of 16.7% of ESBL-producing Enterobacterales in community samples in Blantyre, Malawi, as well as a 4% resistance rate to meropenem [ 17 ]. Among 137 residents in 6 nursing homes in Crete, Greece, Moschou et al, reported rectal colonization by multidrug-resistant microorganisms in 18% of 255 isolates, primarily extended-spectrum-lactamase (ESBL)-producing organisms (26%) [ 18 ].…”
Section: Antimicrobial-resistant Bacteriamentioning
confidence: 99%